(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article provides information about the frequency of out-of-hospital bilateral interstitial pneumonia in terms of age and sex, and its serious harm to human health. Also, the hypercoagulability state, which plays an important role in the pathogenesis of the disease, its essence, and the changes in the blood coagulation system during the formation of the hypercoagulability state were analyzed in the youth section. The role of parameters of the coagulation system in diagnosis and evaluation of the effectiveness of treatment is given.